Assessing the sociology of sport: On sports violence and ways of seeing. (June 2015) - Young, Kevin
On the 50th anniversary of the ISSA and IRSS, a scholar central to the understanding of deviance and violence in sport, Kevin Young, considers the trajectory, challenges and future for research on sport violence. He notes that the sociology of sports violence has been surprisingly limited in its scope, with focus often on football hooliganism and ice hockey tactics. In considering the challenges of sport-related violence, Young notes confounding issues of access and candor in reporting, and interrogates Berger's notion of 'ways of seeing' to provoke new lenses for approaching and understanding the cultures and contexts of violence in sport. In addition, it is argued that using an approach that combines criminology, social justice and community health concerns is crucial to sociological inquiry. The essay closes with key arguments for the study of sport-related violence to 'open the lens' by looking beyond the 'predictable crucibles' of the UK and North America to examine the permutations of culturally embedded violence that link to sport across the globe.